POPPY BEAKERS IN ALSACE: Some points of interest in ceramics research in eastern and north-central France - P. Symonds, Robin (Rei Cretariae Romanae Fautorum Acta, 2024)
The dichotomy between fine wares of Gaulish origin and contemporary fine wares from Germany has always seemed important for the study of both imported pottery in Britain and of the influences and origins of fine wares made in Britain. Among this writer’s early experiences with Roman-period ceramics was the study of the contents of a large pit or well excavated in the 1976 (SYMONDS ET AL. 1980 fig. 18,12; 22,7) at Towcester, eight miles southwest of Northampton.